A Descriptive Study on Childhood Obesity: Examining Research Gaps, Evaluating Interventions, and Informing Policy for Sustainable Health Outcomes - Hasan, Md Rakibul; Rony, Samir Kumar Sarker; Muna, Moryom Akter; Hassan, Sajid (Asian Journal of Public Health and Nursing, 2025)
Background: Childhood obesity is a critical public health issue, affecting almost 19.7% of children in the United States and 24% of adolescents aged 10–17 in Kentucky. This condition is exacerbated by socioeconomic disparities, food deserts, and limited access to physical activity spaces. Effective intervention requires comprehensive, multilevel strategies that involve schools, families, healthcare providers, and policymakers to address systemic barriers and promote equity. Methods: This study utilized a mixed-methods approach, incorporating descriptive statistical analysis from the Centers for Disease Control and Prevention (CDC), state-level reports, and targeted online surveys with parents, educators, and healthcare providers in Kentucky. The surveys explored barriers to healthy behaviors, including food accessibility and opportunities for physical activity. Additionally, descriptive case studies of global intervention models, such as Finland’s Schools on the Move and the UK's MEND program, were synthesized to evaluate their scalability and sustainability for local adaptation. Results: The proposed interventions, which include school-based programs, family-centered initiatives, community engagement efforts, and policy reforms like soda taxes, are expected to reduce obesity prevalence, improve psychosocial well-being, and generate sustainable public health benefits. Descriptive evaluations of programs such as ‘Marathon Kids’ indicate improvements in BMI, dietary habits, and physical activity levels, underscoring the effectiveness of collaborative, evidence-based approaches. Conclusion: Addressing childhood obesity necessitates comprehensive, multilevel strategies. Overcoming challenges such as funding, cultural adaptation, and policy enforcement requires rigorous descriptive studies and stakeholder collaboration. This study contributes to bridging research gaps and advocates for a holistic approach to combating childhood obesity, ultimately fostering healthier communities.